Point-of-care endoscopic optical coherence tomography detects changes in mucosal thickness in ARDS due to smoke inhalation and burns. Issue 3 (May 2019) - Choi, Jae Hyek; Chou, Li-Dek; Roberts, Teryn R.; Beely, Brendan M.; Wendorff, Daniel S.; Espinoza, Mark D.; Sieck, Kyle; Dixon, Alexander T.; Burmeister, David; Jordan, Bryan S.; Brenner, Matthew; Chen, Zhongping; et al.
Highlights: Airway mucosal thickness (MT) increases immediately post injury from smoke inhalation injury and thermal burns. Optical coherence tomography (OCT) shows changes in MT before changes in PaO2 to FiO2 Ratio (PFR). MT correlates with PFR, peak inspiratory pressure (PIP), total IV fluid volume, and post-mortem tissue moisture content. OCT is a useful, minimally invasive, diagnostic tool for ARDS due to smoke inhalation injury and thermal burns. Abstract: Background: The prevalence of acute respiratory distress syndrome (ARDS) in mechanically ventilated burn patients is 33%, with mortality varying from 11–46% depending on ARDS severity. Despite the new Berlin definition for ARDS, prompt bedside diagnosis is lacking. We developed and tested a bedside technique of fiberoptic-bronchoscopy-based optical coherence tomography (OCT) measurement of airway mucosal thickness (MT) for diagnosis of ARDS following smoke inhalation injury (SII) and burns. Methods: 16 female Yorkshire pigs received SII and 40% thermal burns. OCT MT and PaO2 -to-FiO2 ratio (PFR) measurements were taken at baseline, after injury, and at 24, 48, and 72 h after injury. Results: Injury led to thickening of MT which was sustained in animals that developed ARDS. Significant correlations were found between MT, PFR, peak inspiratory pressure (PIP), and total infused fluid volume. Conclusions: OCT is a useful tool to quantify MT changes in the airway following SII and burns. OCT may be effective as a diagnostic tool in the early stages of SII-induced ARDS and should be tested in humans.